Activated M-phase-promoting factor (MPF) is exported from the nucleus of starfish oocytes to increase the sensitivity of the Ins(1, 4, 5)P3 receptors. (1st February 2003) - Santella, L.; Ercolano, E.; Lim, D.; Nusco, G.A.; Moccia, F.
Abstract : Starfish oocytes that are extracted from the ovaries are arrested at the prophase of the first meiotic division. At this stage of maturation, they are characterized by a large nucleus called the germinal vesicle. Meiosis resumption (maturation) can be induced in vitro by adding the hormone 1-methyladenine (1-MA) to the seawater in which the oocytes are suspended. Earlier work in our laboratory had detected Ca 2+ increases in both the cytoplasm and the nucleus of the oocytes approx. 2 min after the 1-MA challenge. The nuclear Ca 2+ increase was found to be essential for the continuation of the meiotic cycle, since the injection of bis-( o -aminophenoxy)ethane- N, N, N´, N´ -tetra-acetic acid (BAPTA) into the nuclear compartment completely blocked the re-initiation of the cell cycle. We have recently confirmed, using confocal microscopy, that the cytoplasmic and nuclear Ca 2+ pools are regulated independently and that the nuclear envelope in starfish oocytes is not freely permeated by the Ca 2+ wave that sweeps across the nuclear region. Studies by others have shown that the sensitivity of the Ins(1, 4, 5) P 3 (IP3 ) receptors (IP3 Rs) to IP3 increases during oocyte maturation, so that they release progressively more calcium in response to the injection of IP3, as maturation proceeds. We have now shown that the increased sensitivity of the IP3 Rs may depend on the activation of the cyclin-dependent kinase, MPF (M-phase-promoting factor) that occurs in the nucleus. MPF does not directly phosphorylate IP3 Rs but phosphorylates instead the actin-binding protein actin depolymerization factor (ADF)/cofilin.